2019
DOI: 10.4103/jrpp.jrpp_19_66
|View full text |Cite
|
Sign up to set email alerts
|

The responsibility of clinical pharmacists for the safety of medication use in hospitalized children: A Middle Eastern experience

Abstract: Objective: We aimed to detect and report the frequency of occurrence of drug-related problems (DRPs) in a Middle Eastern University Children's Hospital (Isfahan, Iran) and classify them in terms of their nature and cause to clarify the responsibility of clinical pharmacists for the safe utilization of medications in hospitalized children. Methods: In this cross-sectional study which was carried out in Imam Hossein Children's University Hospital affiliated with Isfahan U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
2
9
3
Order By: Relevance
“…Of patients with at least one DRP, 65.7% had an average of 0.92 ± 0.8 DRP per prescription; this was higher than results in previous studies, which reported 35.6% and 31.6% [ 3 , 5 ]. However, our proportion was lower than that of Jafarian et al, who reported that 80.1% of patients had at least one DRP [ 2 ]. Such disparities may be due to study population, differences in prescribed drugs, classifications, and reference resources used to determine DRPs.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Of patients with at least one DRP, 65.7% had an average of 0.92 ± 0.8 DRP per prescription; this was higher than results in previous studies, which reported 35.6% and 31.6% [ 3 , 5 ]. However, our proportion was lower than that of Jafarian et al, who reported that 80.1% of patients had at least one DRP [ 2 ]. Such disparities may be due to study population, differences in prescribed drugs, classifications, and reference resources used to determine DRPs.…”
Section: Discussioncontrasting
confidence: 86%
“…Patients younger than 6 years old accounted for about 80% of participants, and their mean age was 4.3 ± 3.6. The physiological characteristics and body development in these age groups closely resembled those found between male and female patients, indicating that sex did not affect the risk of DRP occurrences in children [ 2 ]. Among the ICD-10 groups, the highest proportion had respiratory diseases.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, Sinupret drops has still been misused as ear drops or nose drops in our collected cases. Wrong drug delivery is largely responsible for the medication error [21]. As a result, it is strongly recommended to increase warning signs and to strengthen medication education for drug dispensers of pediatric patients.…”
Section: The Duration Of Sinupret Drops Treatmentmentioning
confidence: 99%